The The Assertive Illocutionary Act of Khatib' Islam Preacher’ in Friday Sermons in Baiturohim Mosque of Surakarta - Sri Kuncoro DibyoSarjono Maskuri Maksum (UIN Salatiga, 2024)
This research reports on an assertive illocutionary act performed by khatib ‘Islam preacher’ in Friday sermons in Baiturohim Mosque of Surakarta. This qualitative research aims to elucidate utterance's form, function, and meaning in the assertive illocutionary act of khatibs in Friday sermons at the Baiturohim Mosque of Surakarta. This research scrutinized three khatibs and data on their utterance form, function, meaning and context in the Friday sermon through the pragmatic qualitative approach. The data were collected by natural observation using audio records. The results show that assertive acts represent the main performance, with 148 tokens of illocutionary acts and for 75 assertive illocution acts. The utterance forms of assertive illocutionary act found are performative and constative. It is found 21 utterance functions of assertive illocutionary act including: to state, to compare, to illustrate, to exemplify, to tell, to think, to assume, to explain, to inform, to doubt, to affirm, to judge, to criticize, to conclude, to emphasize, to remind, to analogize, to admit, to accuse, to quote, and to interpret. Every utterance function has a meaning that evokes a religious message: Islam. Suggestions are made to research the assertive illocutionary act of the religious speakers of Christian, Catholic, Hindu or Buddha in their religious sermons.